Strategi Pengembangan Zona KHAS Berciri Melayu Untuk Meningkatkan Industri Halal di Kota Pekanbaru: Model Pentahelix - Nurnasrina Nurnasrina; Jenita Jenita; Erman Erman; Khairul Amri; Nugraheni Restu (ISLAMIC BUSINESS and FINANCE, 2024)
This study aims to determine the strategy in developing Zona Kuliner Halal, Aman dan Sehat (KHAS)characterised by Malay culture in Pekanbaru City using the pentahelix method. The pentahelix approach involves cooperation between the government, academics, business people, indigenous peoples, and the media. This research was conducted in two locations, namely Raun-Raun Culinary Zone on Jl. Arifin Ahmad and Aero Sport Culinary Zone on Jl. Kaharudin Nasution. Data collection methods were observation and interview. In determining the development model or expansion of the Zona Kuliner Halal, Aman dan Sehat (KHAS), the researcher chose the Pentahelix Model, which is a research approach that involves five different parties, namely government, academia, industry, civil society, and the media. The results show that the Malay characterised KHAS zone can enhance the halal industry in Pekanbaru by adopting strict development criteria, effective management strategies, and comprehensive action plans. The application of the pentahelix method proved effective in coordinating and implementing the development of this zone. The analysis shows the importance of coordinated planning, infrastructure arrangement, halal industry cluster development, promotion, effective governance, and the use of technology and innovation. A pentahelix collaboration between government, academia, industry, civil society and media is needed to ensure the success and sustainability of the KHAS zone. This research concludes that the development strategy of KHAS zones characterised by Malay can strengthen cultural identity, attract investment, and encourage economic growth in Pekanbaru City.Keywords: strategy, KHAS Zone, halal industry, pentahelix